2020
DOI: 10.3329/jsr.v12i4.45187
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Conditions and Hydrogeochemistry of the Sombreiro-Warri Deltaic Plain Deposit (Shallow Benin Formation) in the Vicinity of Agbarho, Nigeria

Abstract: Groundwater conditions and hydrogeochemistry in the Sombreiro-Warri Deltaic Plain deposit at the Agbarho area were described with the aid of data obtained from dug wells. Ten dug wells and two surface water locations were sampled for water quality analysis. Regional groundwater flow is from the northeast to southwest direction with local distortion resulting from sustained groundwater withdrawal in more populated areas of the town. pH in surface water range was from 4.9 to 5.4 and that of groundwater from 3.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Moreover excess of nitrate in water may lead to water pollution as shown in Table 2. Previous studies have shown a significant decline of water resources in the study area [18,23,24,25,26,27,28]. Microorganisms are mostly found in surface water.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover excess of nitrate in water may lead to water pollution as shown in Table 2. Previous studies have shown a significant decline of water resources in the study area [18,23,24,25,26,27,28]. Microorganisms are mostly found in surface water.…”
Section: Introductionmentioning
confidence: 90%
“…Most of the activities are in one way or the other connected to modern day development, unlike in decades ago were the quality of water resource was considered fit for various purpose. [28] were of the view that major cations were below maximum permissible limits within the Sombreiro-Warri plains, Warri Delta state. They further stated that the depth to water level within the Sombreiro-Warri plains varies from 1.2 to 6.45 m. [62] pointed out that within the Sombreiro-Warri Deltaic plain sands Cl concentration in groundwater fall below saltwater intrusion bench mark of 130 mg/l, according to [72] .…”
Section: Hydrogeochemical Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The study area is Agbarho in Delta State, which have been slated to host a massive agricultural project. Efobo et al, (2020) have earlier determined the groundwater flow direction and the hydrogeochemistry of this area. However, there is paucity of information on the subsurface lithology and aquifer characteristics of the study area.…”
mentioning
confidence: 99%